Expresión del factor de crecimiento de endotelio vascular y de ciclooxigenasa-2 en pacientes caninos con cáncer mamario - Pereira, M.E. (2021)
It worked with 17 histopathological sections from canine patients with malignant mammary neoplastic. It was evaluated by immunohistochemistry the vascular endothelial growth factor (VEGF), cyclooxygenase-2 (COX-2) expression, estrogen (ER) and progesterone (PR) receptors, Herb2-Neu protooncogene overexpression and p53. The 47 % had positive expression for VEGF, COX-2, Herb2-Neu and p53. This group presented significant differences in relation to the group with negative expression, with a mean survival time of 175 and 850 days respectively. (p=0.009) The 100 % presented negative expression for ER and PR. The 57 % of the simple carcinomas and 100 % of mixed carcinomas presented positive expression for VEGF, COX-2, Herb2-Neu and p53, with lymph node involvement and metastases. The 100 % of the anaplastic carcinomas showed positive expression for VEGF, Herb2-Neu and p53 and negative for COX-2, with lymph node involvement and metastases. Although markers study make it possible to evaluate the risk of metastases, more studies involving a greater number of patients are required to validate or not these findings. The work objective was to investigate the VEGF and COX-2 expression in canine mammary cancer and its association to other marker and metastases risk.